Crimea-Related Investment Arbitration Cases against Russia before International Investment Arbitration Tribunals - I. V. Rachkov; E. I. Rachkova (Московский журнал международного права, 2020)
INTRODUCTION. The article is devoted to the analysis of the position of the Russian Federation in ten investment cases initiated by Ukrainian investors after the events in Crimea in 2014. The article also highlights current trends in the issue of confidentiality of international investment disputes. The authors analyze whether Russian strategy is effective based on the experience of foreign states, and also make assumptions about the enforceability of arbitration awards. Where the tribunals rendered awards on the merits, the authors highlight the problem of recognition and enforcement, and also assess Russia’s the arguments to set aside these awards.MATERIALS AND METHODS. This study is based on arbitral awards and information from public sources,including official press releases and interviews with Russian representatives in connection with the pending investment disputes. The authors employed the historical method, as well as such general scientific methods as analysis, synthesis, analogy, description, modeling.RESEARCH RESULTS. The result of the study is the identification and formulation of patterns in investment disputes with respect to investments in Crimea to which Russia as a party of Russia, the identification of typical arguments of the parties and the conclusions of arbitral tribunals on this type of disputes.DISCUSSION AND CONCLUSIONS. Having analysed the awards rendered against Russia by international investment tribunals, the authors presented an overview of the parties’ arguments that were presented when the arbitration considered the issue of jurisdiction and resolved the dispute on the merits. The authors assessed these arguments in terms of their credibility on the basis of existing in international investment case-law.